1997
DOI: 10.1053/jhep.1997.v25.pm0009021960
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant hepatitis B virus: Recurrence after liver transplantation in two patients also infected with hepatitis delta virus

Abstract: sulted in a decrease in HBV recurrence and improved Liver transplantation for hepatitis B virus (HBV)-resurvival after transplantation. 5 However, despite the use of lated liver disease is complicated by HBV recurrence HBIG, patients with active HBV replication still experienced and, consequently, poor patient and graft survival. Paa high recurrence of HBV infection after liver transplantatients transplanted for hepatitis delta virus (HDV)-retion. lated cirrhosis are reported to have a diminished inciAn intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…HBV‐DNA sequencing of partial or whole HBV genome from patients with FHB showed variable mutations, but failed to confirm a distinct one specifically associated with FHB [111–113]. On the other hand, coinfection of other hepatitis viruses appears a common phenomenon in these patients [114–116].…”
Section: Clinical Implications Of Occult Hbv Infectionmentioning
confidence: 99%
“…HBV‐DNA sequencing of partial or whole HBV genome from patients with FHB showed variable mutations, but failed to confirm a distinct one specifically associated with FHB [111–113]. On the other hand, coinfection of other hepatitis viruses appears a common phenomenon in these patients [114–116].…”
Section: Clinical Implications Of Occult Hbv Infectionmentioning
confidence: 99%
“…This presumably relates to the high prevalence of viral clearance prior to the procedure in the former setting. Reports are conflicting as to whether co‐infection with HDV favours a reduced incidence of hepatitis B recurrence following OLT, consequent to an inhibitory effect on HBV replication 88–91 . In patients in whom viral eradication is not attained pre‐OLT, infection with the precore mutant HBV strain may be associated with more severe post‐OLT disease, with a substantially increased risk of HBV‐related graft loss compared with that associated with wild‐type infection reported in one study 92 .…”
Section: Use Of Liver Transplantationmentioning
confidence: 99%
“…In the early '90, a multicenter European study showed a 32% recurrence rate among HBV-hepatitis D virus (HDV) coinfected patients compared to 53% in patients with HBV infection alone (6). The protective role of HDV infection has been shown only in liver cirrhosis, but not in acute hepatitis B, and it is supposed to be related to the inhibition of HBV replication (7).…”
Section: Introductionmentioning
confidence: 99%